An empirical investigation into the determinants of the capital structure of Chinese listed firms - Fu, Xundi (2007)
Capital structure is an important part on the composition of a firm, and it is considered to have significant impact the cost of capital and market value of the firm. The Chinese listed firms are playing more and more important roles on the stage of Asian or even world economy. The capital structure of these firms has also drawn many scholars attention in recent years. Compared to plenty of empirical research on the determinants of western firms, the research on these Chinese listed firms seems to be much less. In this paper, it focuses on the determinants of capital structure of these Chinese listed firms from micro-economy perspective. The database used in this paper contains 578 firms up to the year 2006. After the analysis, I find the stable explanatory variables on explaining the determinants of capital structure of Chinese listed firms are profitability, size, non-debt tax shields and operating risk of the firm. Among them, profitability and non-debt tax shields both have negative impact on the capital structure, while size and operating risk of the firm both have positive impact on the firm's capital structure. I also find that using different measurement index does have significant impact on the empirical results. Compared to the western countries, the factors which can affect the firms capital structure are similar for these listed firms in China. Western corporate theories do have some power on explaining the capital structure of Chinese listed firms. The static trade-off model is considered to be better in explaining the capital structure of Chinese listed firms.